2021
DOI: 10.3390/cancers13102451
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Value of Measuring Circulating HPV DNA during Chemo-Radiotherapy in Squamous Cell Carcinoma of the Anus

Abstract: Background and purpose: Circulating tumor DNA (ctDNA) is investigated in various cancers. In squamous cell carcinoma of the anus (SCCA) infection with human papilloma virus (HPV) is found in around 90% of cases and here, plasma HPV (pHPV) can be used as ctDNA. Preliminary data have proved the ability to detect pHPV16 and -18 in SCCA. We have developed a highly sensitive method for measurement of six relevant pHPV subtypes, to investigate the elimination pattern of pHPV during chemo-radiotherapy (CRT) for SCCA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 37 publications
0
33
0
Order By: Relevance
“…Biomarkers and patient-reported outcomes also emerged as recent trend topics in ASCC. The HPV/p16 status, tumor-infiltrating lymphocytes (TILs) rate, Epidermal Growth Factor Receptor (EGFR) overexpression, circulating HPV-DNA and blood biomarkers [Neutrophil-to-lymphocyte ratio (NLR), Systemic Index of Inflammation (SII), absolute number of leukocytes and neutrophils, hemoglobin level] were the most frequently studied biomarkers [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Biomarkers and patient-reported outcomes also emerged as recent trend topics in ASCC. The HPV/p16 status, tumor-infiltrating lymphocytes (TILs) rate, Epidermal Growth Factor Receptor (EGFR) overexpression, circulating HPV-DNA and blood biomarkers [Neutrophil-to-lymphocyte ratio (NLR), Systemic Index of Inflammation (SII), absolute number of leukocytes and neutrophils, hemoglobin level] were the most frequently studied biomarkers [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further intensification of the local treatment (to lower the risk of local failures) should also be considered in future studies, by exploring new radiotherapy techniques and concomitant systemic options like immunotherapy [25,26]. Nevertheless, there is an urgent need for tools to improve the selection of patients who will benefit from ICT prior to CRT [27,28].…”
Section: Discussionmentioning
confidence: 99%
“… 2 , 9 , 10 , 11 , 12 Researchers have reported that some hematological and immunohistochemical indicators may play a prognostic role in patients with ASCC who received definitive treatment. 13 , 14 , 15 Casadei‐Gardini et al enrolled 308 ASCC patients to develop a logistic nomogram using the pre‐treatment systemic inflammation index (platelet × neutrophil/lymphocyte), pre‐treatment nodal status and pre‐treatment hemoglobin levels in order to predict the prognosis of patients treated with concurrent chemoradiation. 16 However, for patients newly diagnosed with ASCC, there is a lack of effective prognostic models to better predict individual patient survival outcomes.…”
Section: Introductionmentioning
confidence: 99%